Knocking out maxillary third molar with a hockey stick elevator - Vaibhav Jain; Joel D'Silva; Himani Garg; Joyce Pinky Mendonsa (Wolters Kluwer Medknow Publications, 2016)
Extraction of maxillary third molar always comes as a challenge for any dental practitioner owing to its limited accessibility and minimal space for instrument placement. Moreover, the complications related to faulty extraction technique can never be ignored. We have here described a simple and easy method of extraction of the maxillary third molar tooth using hockey stick elevators which can solve most of the problems that are faced by dental surgeons in the extraction of maxillary third molars. This technique has proved its efficacy and has been time tested for removal of a maxillary third molar providing a good alternative for routine extraction techniques of maxillary third molars.